Increasing Public Awareness of the Importance of "Gemari" (Love to Eat Fish) Through Mentoring Catfish Cultivation and Processing - Candra Wahyuni; Retno Palupi Yonni Siwi (Journal of Community Engagement in Health, 2024)
Catfish is one type of freshwater fish that is much loved by the people of Indonesia. In addition to its delicious taste and easy to process, this type of fish also has a lot of nutrients in it that are good for body health. Catfish farming is a maintenance activity for catfish enlargement from small in size (fry) to consumption size. Catfish farming is one of the efforts to provide food needs as a source of protein. Protein sources from fish are increasing day by day, along with increasing public awareness about the importance of catfish's nutritional content. The method used in this community service activity is by providing counseling, handing over catfish seeds, and assisting catfish processing as a health promotion medium. The results of Community Service activities regarding catfish farming, processing methods, and understanding of the high nutritional content in catfish can increase family interest in catfish consumption through fondness for eating fish.